2022
DOI: 10.3390/ijerph19053041
|View full text |Cite
|
Sign up to set email alerts
|

Age Diversity Climate Affecting Individual-Level Work-Related Outcomes

Abstract: The present study answers the call for more studies to investigate the age diversity climate’s effect on individual-level outcomes. Building on the social identity approach and social exchange theory, we surveyed 110 Italian employees aged between 18 and 61 years old (M = 46.10, SD = 10.02) and investigated the role of age diversity climate in predicting intentions to quit (H1), job-related wellbeing (H2), and work engagement (H3). Our findings confirmed the hypotheses (H1 and H2), showing the added effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
1
1
1
Order By: Relevance
“…Therefore, we affirmed hypotheses H6a and H6b. Our study supports previous research results that show a positive relation between both experience Mo, et al [106] and age Bellotti, et al [107] and the turnover intention of the individual in a toxic workplace environment. It may be because employees with more experience know their fields and may find job opportunities in other organizations and other benefits or retire instead of continuing to work in a toxic workplace environment with cognitive distraction under the influence of despotic leadership.…”
Section: Theoretical Additionsupporting
confidence: 92%
“…Therefore, we affirmed hypotheses H6a and H6b. Our study supports previous research results that show a positive relation between both experience Mo, et al [106] and age Bellotti, et al [107] and the turnover intention of the individual in a toxic workplace environment. It may be because employees with more experience know their fields and may find job opportunities in other organizations and other benefits or retire instead of continuing to work in a toxic workplace environment with cognitive distraction under the influence of despotic leadership.…”
Section: Theoretical Additionsupporting
confidence: 92%
“…For example, Wegge and Meyer (2020) reported inconclusive outcomes in the absence of more dimensions within the age diversity that required examination before conclusively indicating the outcome. While some studies reported a positive relationship between age diversity and performance outcomes (Bellotti et al, 2022;Sousa et al, 2021), results from the present study indicated contrarian results. The authors' findings appear consistent with other studies.…”
Section: Discussioncontrasting
confidence: 84%
“…First, while previous studies on age diversity climate have shown that creating an environment where individuals of all ages are fairly treated can foster organizational-level work-related outcomes (Boehm et al, 2014; Profili et al, 2016), with this study we focus on the effect that perceptions of an age-inclusive context have on a key individual level work-related outcome (i.e. engagement), contributing to gaining a better understanding of a far less commonly explored relationship (Bellotti et al, 2022). Second, we expand previous findings on the relationship between age-related climate and work outcomes by examining how, at the individual level, the interrelation between perceptions of fair treatment with respect to age and two objective age-related factors (i.e.…”
Section: Discussionmentioning
confidence: 99%